Dependency of the thermal and electrical conductivity on temperatures and compositions of Zn in the Al−Zn alloys. (4th March 2019) - Erol, H.; Çadirli, E.; Erol, E.A.; Gündüz, M.
ABSTRACT: The variations of thermal conductivity (K) with temperature for Al–xZn (x = 5, 10, 20, 30, 50 and 60 wt. %) alloys were measured by using a radial heat flow furnace. The variations of electrical conductivity (σ) of solid phases with temperature for the studied alloys were determined from the Wiedemann-Franz and Smith-Palmer equations by using the measured values of K from the plots of K. The thermal temperature coefficient (αTTC ) and the electrical temperature coefficient (αETC ) were obtained. Dependency of the αTTC and αETC on the composition of Zn in the Al−Zn alloys was also investigated. According to the present experimental results, K of Al–Zn alloys linearly decrease with increasing temperatures up to the melting temperature for each composition and exponentially decrease with the increasing Zn content. On the other hand, the σ of Al based Al-Zn alloys exponentially decrease with increasing temperature and Zn content.